Quantitative Models for Accounting Control. - Onsi, Mohamed (The Accounting Review, 1967)
Abstract This article presents a quantitative model for accounting control which is an important function of accounting. It is defined as that process which discovers and reports information enabling managers to correct or prevent unfavorable conditions. This article also examines the basic control aspects of three control models, (1) the traditional accounting model employing standard costing, (2) an accounting model based on classical statistical theory, and (3) an accounting control model based on modern decision theory. Two criteria are currently used to decide whether to investigate deviations from standard. They are, the absolute size of a deviation or the relative size of a deviation, unfavorable or favorable. The magnitude of these criteria depend upon management judgment and experience. The accounting control model based on classical statistics assumes that standard cost is equal to the mean of a normal probability distribution, standards are developed as ranges, not as point-estimates.